Nusyuz dalam Al-Qur’an - Zainuddin Zainuddin; Ummi Khoiriah (Program Studi Ilmu Al-Qur'an dan Tafsir Fakultas Ushuluddin dan Filsafat, UIN Ar-Raniry, 2017)
Marriage is an inner and outer bond between a man and a woman with the aim of forming a happy and eternal family based on the One Godhead. In married life, the husband is responsible for fulfilling the rights of his wife, and vice versa for the creation of a sakinah, mawaddah wa rahmah family. However, what is common between husband and wife interactions is disputes over nusyuz. The method used in this discussion is the maudhu'i method. The results of this study are the completion of the wife's nusyuz in Surat al-Nisa': 34 which is touching advice from the husband, the husband's neglect of his wife in bed not outside the room or outside the house, and hitting with a blow that is not painful, does not leave an impression and not on the face. However, if the first method succeeds in making the wife return to obedience, the husband does not need to use the second or third step. While the completion of the husband's nusyuz in the letter al-Nisa ': 128 is the peace that is expected to emerge from the wife. The wife gave up some of her rights over her husband not to be fulfilled so that the ties of marriage between the two remained intertwined. Both are balanced when viewed from the goal to be achieved, namely maintaining the integrity of the household. However, the difference in the method cannot be said to be wrong, because the nature of men and women are basically different. So, the solution to the problem is also different according to the needs of both. Perkawinan merupakan ikatan lahir batin antara seorang pria dan wanita dengan tujuan membentuk keluarga yang bahagia dan kekal berdasarkan Ketuhanan Yang Maha Esa. Dalam kehidupan berumah tangga, suami bertanggungjawab memenuhi hak istrinya, begitu juga sebaliknya demi terciptanya keluarga sakinah, mawaddah wa rahmah. Namun, lazim terjadi di antara interaksi suami dan istri adalah perselisihan karena nusyuz. Metode yang digunakan dalam pembahasan ini adalah metode maudhu’i. Hasil dari penelitian ini adalah penyelesaian nusyuz istri pada surat al-Nisa’: 34 ialah nasihat yang menyentuh dari suami, pengabaian suami kepada istri di tempat tidur bukan di luar kamar ataupun di luar rumah, dan memukul dengan pukulan yang tidak menyakitkan, tidak membekas serta bukan di wajah. Namun, jika cara pertama berhasil membuat istri kembali taat, suami tidak perlu menggunakan langkah kedua maupun ketiga. Sedangkan penyelesaian nusyuz suami pada surat al-Nisa’: 128 yaitu perdamaian yang diharapkan muncul dari istri. Istri merelakan sebagian haknya atas suami tidak ditunaikan agar ikatan pernikahan keduanya tetap terjalin. Keduanya seimbang jika dilihat dari tujuan yang ingin dicapai, yaitu mempertahankan keutuhan rumah tangga. Namun, perbedaan cara tersebut juga tidak dapat dikatakan salah, karena tabiat laki-laki dan perempuan pada dasarnya berbeda. Maka, penyelesaian masalah juga berbeda menyesuaikan kebutuhan keduanya.